Protection of the Right to Privacy in the Digital Age: Reflection on the Vietnamese Context - Lê, Trần Như Tuyên (2020)
The first step is to understand basic theoretical issues of the privacy and the importance of protecting privacy in the Digital Age. Secondly, analyzing the impacts on privacy of digital and the need for legislation of privacy in Digital Age. Thirdly, clarify the current situation of privacy and some urgent issues in the implementation of protecting the right to privacy under Vietnamese Laws. Finally, attempts to find some suitable and feasible orientations and solutions to contribute to protecting the right to privacy in a more effective way. The result of this study will provide scientific arguments on the right to privacy to contribute to protecting this right in accordance with the laws in new era.